Study on shock initiation of the charge covered by metal plate with penetrated notch. (March 2020) - Chen, X W; Wang, J X; Tang, K; Wang, H F; Li, Y B
Abstract: To analyze the coupling damage effect of high-speed fragments and near-field strong shock wave on the covered charge, a theoretical model of the shock initiation of the charge covered by metal plate with defects was established. The defect of the covered plate was simplified as a penetration notch, and the evolution characteristics of the shock wave in the notch were analyzed theoretically. The critical condition of the explosive detonation was determined by combining the explosive initiation criterion and the shock wave evolution characteristics. Take TNT covered by steel plate with a penetrated notch as an example, the nonlinear finite element program was used to simulate the shock initiation process of pressed charge, and the validity of the numerical simulation was verified by experimental results. The influence of the intensity of the shock wave, the thickness of the covered metal plate as well as the geometrical characteristics of the penetrated notch on the shock initiation of the pressed charge were analyzed by combining the theoretical model and numerical simulation results. The relationship of the notch size of the covered plate and the detonation distance was obtained by fitting, and the parameters n and K of the critical initiation criterion were obtained by least squares method. The theoretical calculation results and the numerical simulation results are agree with each other well and show that, the covered metal plate is beneficial for the protection of the charge. The existence of notch will weaken the protective performance of the covered plate, and the shape and size of the notch are also important factors that will affect the critical detonation distance of the charge. For the pressed TNT with and without 45# steel covered plate with the thickness 3 millimeters, the critical detonation distance of non-contact explosion was 13 millimeters and 81 millimeters, respectively. For the covered plate with a cylindrical notch, the critical detonation distance of the pressed TNT increases with increase of the diameter of the covered plate. For the covered plate has a frustum notch, the critical detonation distance of the pressed TNT decreases with increase of the slope in normal reflection.